THE CONTENT AND STRUCTURE OF THE PREPARATION OF THE PRESCHOOLER FOR ACTIVITIES ON CHILDREN'S HYGIENE - Tadjibaeva Gavharoy Ismailovna (International Scientific and Current Research Conferences, 2022)
The problem of a healthy lifestyle – the most important problem facing a person – is the problem of comprehensive personal development, the formation of a socially and hygienically rational lifestyle in the field of working life and recreation, which contributes to the strengthening of scientifically based, socially hygienic activities.